PELAYANAN SURVEI PENGUKURAN DAN PEMETAAN TANAH - Sirait, Robert Hasudungan (Jurnal Ilmu Administrasi Negara, 2016)
Measurement Survey and Mapping Services Land. This study aims to investigate the implementation of survey services measurement and mapping of land at the Land Office Pekanbaru and factors inhibiting the implementation of the service. The method used is qualitative method. Source data extracted from key informants. Community, service counter clerk, the clerk cekplot, measuring officers, community leaders and witnesses border. The technique of collecting data using interview techniques, investigation and observation, while data analysis techniques using qualitative techniques with a descriptive approach. Based on the survey results revealed that the implementation of service measurement and mapping of land at the Land Office Pekanbaru given to the community is pretty good. While the factors inhibiting the implementation of measurement and mapping services in the Land Office Pekanbaru among other factors shortage of skilled human resources, and the ability of the applicant to provide the completeness of the application. This is summarized in the awareness factor, rules, organizational and revenue, personnel skills and factors means.